2018
DOI: 10.1007/s00595-018-1650-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical outcomes of esophagectomy and chemoradiotherapy after noncurative endoscopic submucosal dissection for esophageal squamous cell carcinoma

Abstract: PurposeEndoscopic submucosal dissection (ESD) is widely used to treat esophageal cancer, but some patients require additional treatment due to the possibility of lymph node metastasis. The aim of this study was to elucidate the clinical outcomes of these additional treatments.MethodsThe study included 59 patients who developed superficial esophageal squamous cell carcinoma after noncurative ESD treated between 2005 and 2016, of whom 28 underwent esophagectomy and 31 received chemoradiotherapy (CRT).ResultsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…The metastasis rates for each group were 12/216 (5.6%, 95% CI: 2.9–9.5%) in the follow‐up observation group (six reports; Table ), 0/6 in the additional surgical resection group (three reports; 0%, 95% CI: 0–46.0%), and 1/17 in the additional chemoradiotherapy group (six reports; 5.9%, 95% CI: 0.2–28.7%) (Table ).…”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
See 3 more Smart Citations
“…The metastasis rates for each group were 12/216 (5.6%, 95% CI: 2.9–9.5%) in the follow‐up observation group (six reports; Table ), 0/6 in the additional surgical resection group (three reports; 0%, 95% CI: 0–46.0%), and 1/17 in the additional chemoradiotherapy group (six reports; 5.9%, 95% CI: 0.2–28.7%) (Table ).…”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…Furthermore, after contacting the authors, we also tabulated the data for the follow‐up observation, additional surgical resection, and additional chemoradiotherapy groups for patients with pMM cancer with vascular invasion and pVM0 esophageal squamous cell carcinoma following ER. Metastasis occurred in 3/14 patients (21.4%, 95% CI: 4.7–50.8%) in the follow‐up observation group (four reports), 1/20 patients in the additional surgical resection group (four reports; 5.0%, 95% CI: 0.1–24.9%), and 7/45 patients in the additional chemoradiotherapy group (six reports; 15.6%, 95% CI: 6.5–29.5%) (Table ).…”
Section: Part 1: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
See 2 more Smart Citations
“…Some possible reasons include poor physical or mental conditions, substantial economic burden, intolerance to surgery or CRT, and higher rates of comorbidities and adverse events following additional treatment. Koterazawa et al [13] reported that the incidence of anastomotic leakage, pulmonary complications, and recurrent nerve palsy among patients who underwent esophagectomy after ESD was 17.8, 28.5, and 10.7%, respectively. Other studies have indicated that elderly patients (aged 70 years or more) who underwent esophagectomy experienced higher rates of adverse events, operative mortality, and in-hospital mortality, as well as lower 5-year survival rate [14, 15].…”
Section: Discussionmentioning
confidence: 99%